2012
DOI: 10.1080/10826068.2011.563639
|View full text |Cite
|
Sign up to set email alerts
|

PURIFICATION AND CHARACTERIZATION OF DDT-DEHYDROHALOGENASE FROMPseudomonas putidaT5

Abstract: DDT-dehydrohalogenase is involved in the catalytic degradation of p,p'-DDT by eliminating either HCl or Cl(-) to form DDD/DDE. Isolation, purification and characterization of DDT-dehydrohalogenase from a bacterial source is reported in this manuscript. Ten bacterial cultures belonging to DDT degrading microbial consortium were screened for the DDT-dehydrohalogenase activity. Among these, the clarified cell homogenate of Pseudomonas putida T5 showed higher DDT-dehydrohalogenase activity and enzyme was purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…3b ). Several similar studies on the biodegradation mechanism of DDT have been conducted by GC-MS. Rangachary et al 20 reported that the strain Pseudomonas putida T5 could transform DDT to DDE or DDD by eliminating either HCl or Cl - . Fang et al 13 reported that the strain Sphingobacterium sp.…”
Section: Resultsmentioning
confidence: 99%
“…3b ). Several similar studies on the biodegradation mechanism of DDT have been conducted by GC-MS. Rangachary et al 20 reported that the strain Pseudomonas putida T5 could transform DDT to DDE or DDD by eliminating either HCl or Cl - . Fang et al 13 reported that the strain Sphingobacterium sp.…”
Section: Resultsmentioning
confidence: 99%